The “Latina Madwoman” at the Crossroads of Harm and Hope - Rubóczki, Babett (Hungarian Journal of English and American Studies, 2021)
Book review:Halperin, Laura. Intersections of Harm: Narratives of Latina Deviance and Defiance. New Brunswick: Rutgers UP, 2015. xii + 238 pages. ISBN 978-0-8135-7036-5. Pbk. $29.95.